2017
DOI: 10.1136/thoraxjnl-2015-207682
|View full text |Cite
|
Sign up to set email alerts
|

CXCL14 is a candidate biomarker for Hedgehog signalling in idiopathic pulmonary fibrosis

Abstract: Post-results, NCT00968981.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 52 publications
2
31
1
Order By: Relevance
“…Similar to the results of previous studies, [24][25][26][27][28] we demonstrated that the Hh pathway was activated during pulmonary fibrosis through the study of SSc-ILD patients. TGF-b1 signaling has been confirmed to play a crucial and indispensable role in the pathogenesis of lung fibrosis 29,30 and pirfenidone has consistently been demonstrated to possess the ability to modulate this canonical pathway property by suppressing TGF-b1.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the results of previous studies, [24][25][26][27][28] we demonstrated that the Hh pathway was activated during pulmonary fibrosis through the study of SSc-ILD patients. TGF-b1 signaling has been confirmed to play a crucial and indispensable role in the pathogenesis of lung fibrosis 29,30 and pirfenidone has consistently been demonstrated to possess the ability to modulate this canonical pathway property by suppressing TGF-b1.…”
Section: Discussionsupporting
confidence: 91%
“…We provide a single cell atlas of Idiopathic Pulmonary Fibrosis (IPF), a fatal interstitial lung disease, focusing on resident lung cell populations. By profiling 312,928 cells from 32 IPF, 29 healthy control and 18 chronic obstructive pulmonary disease (COPD) lungs, we demonstrate 25 that IPF is characterized by changes in discrete subpopulations of cells in the three major parenchymal compartments: the epithelium, endothelium and stroma. Among epithelial cells, we identify a novel population of IPF enriched aberrant basaloid cells that co-express basal epithelial markers, mesenchymal markers, senescence markers, developmental transcription factors and are located at the edge of myofibroblast foci in the IPF lung.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating chemokine ligand (C‐X‐C motif) 14 (CXCL14), also known as BRAK (breast and kidney‐expressed chemokine), is a ligand of CXCR4 and acts as an autocrine stimulator for fibroblast proproliferation and migration, which accelerates epithelial‐to‐mesenchymal transition and facilitates the recruitment of fibrocytes. Evidence suggests that CXCL14 predicts the activation of the hedgehog (Hh) signaling pathway and, thus, can be used to monitor the Hh antagonist therapy in IPF . However, the roles of CXCL14 in IPF have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%